2010
DOI: 10.1016/j.biocel.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

TLRs and chronic inflammation

Abstract: After the discovery of Toll-like receptors (TLRs), innate immune mechanisms came back in the focus of scientific research. With more and more mechanisms of TLR biology known, it has become clear that these and also other innate immune receptors are not only of crucial importance in the immune response to invading pathogens, but also play a role in the homeostasis of commensal flora and in the response to stress and danger signals. In this respect, increasing evidence is found that inappropriate quantity or qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 163 publications
(147 reference statements)
2
129
0
5
Order By: Relevance
“…Dysregulation of TLR signaling pathways leads to increased expression of cytokines and chemokines, causing tissue damage and chronic inflammation (18). As a number of studies have shown, when TLRs are stimulated, there is a concomitant activation of inflammatory and anti-inflammatory pathways (28), the latter being needed to limit the inflammatory response and avoid tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of TLR signaling pathways leads to increased expression of cytokines and chemokines, causing tissue damage and chronic inflammation (18). As a number of studies have shown, when TLRs are stimulated, there is a concomitant activation of inflammatory and anti-inflammatory pathways (28), the latter being needed to limit the inflammatory response and avoid tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The amount and type of cytokines released after the TLR activation regulate the differentiation and functional state of dendritic cells and influence T cell activation and differentiation (17). Aberrant stimulation of TLRs or dysregulation of TLR signaling pathways results in increased expression of cytokines and chemokines, creating a vicious inflammatory cycle that contributes to the initiation and progression of chronic inflammatory diseases and autoimmune diseases such as rheumatoid arthritis (18,19).…”
mentioning
confidence: 99%
“…The ligand of this complex is however not yet known. TLR1 is expressed in leukocytes and in non-immune cells such as astrocytes, fibroblasts, keratinocytes, endothelial and epithelial cells (Ospelt and Gay, 2008b). It was found to be expressed also by synovial fibroblasts, including RASF (Ospelt et al, 2008).…”
Section: Toll-like Receptors (Tlr) In Ramentioning
confidence: 99%
“…In individuals positive for HLA-DRβ smoking significantly increases the risk of developing RA (Klareskog et al, 2006). On the other hand smoking might induce ligands to trigger TLR signalling (Ospelt and Gay, 2008b). In conclusion, the latest research proving the involvement of the innate immune system into the pathogenesis of RA contributes to a better understanding of the initiation of the disease as well as might point to possible targets for novel therapies in RA.…”
Section: Shared Epitopes As Part Of Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation